Psycho-cybernetics and self fulfillment - "Maltz, Maxwell" (Toranto, 1985)
All of us face frustrations in our daily lives, but it is how we deal with them that makes the vital difference between success and failure. Some persons limit themselves, forever keeping themselves from achieving their highest potential. These are persons with low opinions of themselves, with limited expectations. Al of us respect and admire someone of quite a different nature- the man who derives great satisfaction as he achieves the goals he sets for himself
Keywords: Self acceptance